2020
DOI: 10.48550/arxiv.2009.05617
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unit Test Case Generation with Transformers and Focal Context

Abstract: Automated Unit Test Case generation has been the focus of extensive literature within the research community. Existing approaches are usually guided by the test coverage criteria, generating synthetic test cases that are often difficult to read or understand for developers.In this paper we propose ATHENATEST, an approach that aims at generating unit test cases by learning from real-world, developer-written test cases. Our approach relies on a state-ofthe-art sequence-to-sequence transformer model which is able… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…In practice we found that both AthenaTests whole test generation and the seq2seq assertion model generated many tests and oracles that were not executable. The AthenaTest authors noted this issue in their evaluation, where they found that only 16% of the generated test cases were executable without errors and actively tested the unit under test [21]. The oracle generation model generated 34% executable oracles, and of these we observed that a further 5% were tautologies, resulting in an overall yield of 29% potentially meaningful oracles.…”
Section: Rq3: Bug Detectionmentioning
confidence: 95%
See 4 more Smart Citations
“…In practice we found that both AthenaTests whole test generation and the seq2seq assertion model generated many tests and oracles that were not executable. The AthenaTest authors noted this issue in their evaluation, where they found that only 16% of the generated test cases were executable without errors and actively tested the unit under test [21]. The oracle generation model generated 34% executable oracles, and of these we observed that a further 5% were tautologies, resulting in an overall yield of 29% potentially meaningful oracles.…”
Section: Rq3: Bug Detectionmentioning
confidence: 95%
“…Lastly, AthenaTest [21] is a transformer model approach to generate entire unit tests including both prefixes and oracles. AthenaTest takes as input the unit's context (e.g., surrounding class, method signatures, etc.…”
Section: Neural Methodsmentioning
confidence: 99%
See 3 more Smart Citations